Alzheimer’s Disease Biomarkers Revisited From the Amyloid Cascade Hypothesis Standpoint - Alawode, Deborah O. T.; Fox, Nick C.; Zetterberg, Henrik; Heslegrave, Amanda J. (Frontiers in Neuroscience, 2022)
Alzheimer’s disease (AD) is the most common neurodegenerative disease worldwide. Amyloid beta (Aβ) is one of the proteins which aggregate in AD, and its key role in the disease pathogenesis is highlighted in the amyloid cascade hypothesis, which states that the deposition of Aβ in the brain parenchyma is a crucial initiating step in the future development of AD. The sensitivity of instruments used to measure proteins in blood and CSF has significantly improved, such that Aβ can now successfully be measured in plasma. However, due to the peripheral production of Aβ, there is significant overlap between diagnostic groups. The presence of pathological Aβ within the AD brain has several effects on the cells and surrounding tissue. Therefore, it is possible that using markers of tissue responses to amyloid may reveal more information about Aβ pathology and pathogenesis than looking at plasma Aβ alone. In this review paper, we will explore the concept of Aβ being the cause of AD, using the amyloid cascade hypothesis as a starting point, and delve into how the effect of Aβ on the surrounding tissue can be monitored using biomarkers. In particular, we will consider whether glial fibrillary acidic protein, triggering receptor expressed on myeloid cells 2, phosphorylated tau and neurofilament light chain could be used to phenotype and quantify the tissue response against Aβ pathology in AD.